'My laptop is an extension of my memory and self': Post-Internet identity, virtual intimacy and digital queering in online popular music. Issue 2 (19th June 2017) - Waugh, Michael
Abstract: This article studies the ways that Post-Internet ideas inform much contemporary musical production. Drawing on interviews conducted with musicians/artists self-consciously highlighting Post-Internet themes in their work, including Arca, Ryan Trecartin, 18+, Holly Herndon and ADR, the paper emphasises the significance of the term 'Post-Internet' for contemporary identity politics. It outlines the Post-Internet ideas of Karen Archey, Robin Peckham and Nathan Jurgenson, illuminating their indebtedness to posthuman discourses through a study of the music of Holly Herndon. It then introduces the notion of 'digital queering', a trend located in the work of many Post-Internet musicians. Mykki Blanco, 18+, Arca and Ryan Trecartin fuse the posthumanism of Post-Internet identity with the fluid gender deconstructions of queer theory. This is inspired by the ability to perform multiple 'selves' online as well as the intimate relationship with digital networks that is a consequence of Post-Internet ideas.